Industry mobility and disability benefits in heavy manual jobs: A cohort study of Swedish construction workers - Söderberg, Mia; Stattin, Mikael; Robroek, Suzan JW; Burdorf, Alex; Järvholm, Bengt (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVES ': 'This study aimed to investigate whether change from the construction industry to work in other industries at age 45–55 years lowered risks of disability benefits (DB) later in life (60–64 years of age). We hypothesized that risks would be lowered the most among those changing from the heaviest occupations. ' ' METHODS ': 'The study included men employed in the construction industry during 1971–1993. We selected workers from the largest occupational groups in heavy (concrete workers and painters) and less heavy (drivers, electricians and foremen) occupations. The occurrence of DB in 1990–2015 was retrieved from national registers. Regression analyses were used to calculate relative risks (RR) of DB at 60–64 years, comparing those working in other industries to those still in the construction industry at the age of 45, 50 and 55 years. ' ' RESULTS ': 'Shifting out of from the construction industry was related to lowered DB risks at 60–64 years in all selected occupations. Effects were most pronounced among those who, at 55 years of age, worked in an industry other than construction, with significantly reduced RR for DB among concrete workers [RR 0.63, 95% confidence interval (CI) 0.51–0.77], electricians (RR 0.61, 95% CI 0.47–0.77) and foremen (RR 0.78, 95% 0.63–0.96). ' ' CONCLUSIONS ': 'Risks for DB at 60–64 years of age were reduced among those who changed from construction work to other industries. Notable reductions were observed among workers originating from both heavy and less heavy occupations, and future studies should explore other factors, in addition to heavy workload, as motivators for leaving the construction industry.
Keywords: cohort study; construction industry; construction worker; disability benefit; heavy manual job; heavy work; industry mobility; Sweden; work ability